Network structure and urban mobility sustainability: A topological analysis of cities from the urban mobility readiness index (2025)
In the context of rapid urbanization, efficient and sustainable urban mobility is critical. This study explores the impact of urban network structure and socio-demographic factors on Urban Mobility Readiness (UMRi) across 62 cities worldwide. Using complex network analysis, Principal Component Analysis, and multiple linear regression models, we identify significant relationships between network metrics — such as average node degree, clustering coefficient, and graph diameter — and urban mobility performance. Cities with denser, more interconnected networks tend to achieve higher UMRi scores, indicating better preparedness for modern mobility challenges. Our findings also highlight the importance of economic resources, with GDP per capita emerging as a significant predictor of UMRi. Cities with well-funded and well-designed transportation networks demonstrate stronger performance in terms of mobility readiness and sustainability. Conversely, cities with more dispersed networks face greater challenges in optimizing their transportation systems. These insights underscore the importance of compact, resilient networks that promote accessibility and efficiency. This study emphasizes the critical role of network structure in shaping urban mobility outcomes and offers strategic guidance for enhancing transportation systems in rapidly growing urban areas. Future research should focus on integrating emerging technologies, such as autonomous vehicles and smart city solutions, to further optimize urban mobility. This approach offers a novel perspective on how the structure of urban networks influences the sustainability and efficiency of public transport in diverse urban contexts.